PERTUNJUKAN IMAM SHOLAT DAN TAFSIR POLITIK JAMAAH - Rohim, Syaiful (Analisis: Jurnal Studi Keislaman, 2014)
PRAYER LEADER AND THE INTERPRETATION OF POLITICAL CONGREGATION.  Being a religious leader is not dissimilar  to  being  a social  leader.  Besides  he has to  perform religius duties personally,   he also received an additional  task to carry out the functions of religious leadership in accordance with the social capacity he has in his social group.  In the social space, ritual practices are actually not dissimilar to other social behavior, especially in the process of interaction and subjective meanings of symbols. When a person is interacting, the behavior that he played in performing religious rituals- for example became a prayer leader - actually  remains  in the frame   of “interaction  order” to meet the “self-perfection”. This article reviewed the symbolic meaning of leadership  in the  practice  of prayer.  By using interpretative paradigm of Lindlof  in the phenomenological research tradition, the  authors    classify   the  prayer  leadership  typology  based on specific symbols and behavior, namely: “conditional  compromise leader”, “Image-Sensational leader”, “autonomus leader”, and “Ideal-literalists leader”.